The Effect of Physical and Mental Health Programs and Career Support on Employee Wellbeing and Loyalty in the Creative Industries in Jakarta - Faridah Faridah; Rani Eka Arini; Muhamad Ammar Muhtadi (West Science Social and Humanities Studies, 2024)
This study examines the effects of physical and mental health programs and career support on employee wellbeing and loyalty in Jakarta’s creative industries. Using a quantitative approach with 180 respondents, data was collected through a Likert scale-based questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results indicate that both physical and mental health programs and career support significantly influence employee wellbeing, which in turn has a strong positive effect on loyalty. Additionally, wellbeing mediates the relationship between support programs and loyalty, underscoring the importance of a holistic approach to employee support. Career support showed the strongest impact on both wellbeing and loyalty, suggesting that professional development opportunities are crucial in retaining talent within the creative sector. These findings provide valuable insights for organizations aiming to improve employee engagement and loyalty through comprehensive support programs that address both health and career needs.